Data for: Scales of landscape influence on Dissolved Organic Carbon Dynamics in Boreal Surface Water - Lackner, Anna (Swedish University of Agricultural Sciences, 2025)
This dataset includes three csv files (PLS_data.csv, 145 rows × 244 columns, High_Resolution_Data_PCA.csv, 145 rows × 73 columns, Soil_moisture_composition.csv, 145 rows × 82 columns) and one .rmd file. The csv files contain catchment characteristics derived from conventional spatial data ( land use, soil type, mean climatic variables, etc...) and high resolution spatial data (stream and ditch network and SLU soil moisture map). The .rmd takes the data for these 145 catchments and performs statistical analysis using PCA and PLS regression. For the .rmd file R is necessary to run the script. For more detailed information, see the readme.md file. Information about the R session is in sessionInfo.txt.

Se engelsk beskrivning och readme.md.
Data for: Scales of landscape influence on Dissolved Organic Carbon Dynamics in Boreal Surface Water
Keywords: SURFACE WATER; spatial distribution; geografisk fördelning; dissolved organic carbon in water; Environmental monitoring facilities; Anläggningar för miljöövervakning; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Geoscientific Information; Geovetenskap; Environment; Miljö; Inland Waters; Sjöar och vattendrag